Hubungan Pengetahuan Keluarga Tentang Diit Hipertensi Dengan Kepatuhan Pemberian Diit Hipertensi Pada Lansia - Puguh Santoso; Nadhirotul Ulfa (coba, 2016)
Hypertension is persistent blood pressure where its systolic pressureabove 140 mmhg and the diastolic is 90 mmhg. Several risk factors cause highpressure blood is getting older and the history of high pressure in family. Familyis the main support system for old person in restraining their health. One problemof managing hypertension is family pursuance in conducting hypertension diet forold person. Therefore, this study is aimed to analyze correlation between familyknowledge on hypertension diet toward pursuance of giving hypertension diet forold person.Design of this study is descriptive analytic study by using cross sectionalapproach. Population of this study is family with hypertension old person in Rt 09Rw 02 Pojok, Kediri. The number of population is 21 respondents; sampling technique used here is Purposive sampling that it is obtained 20 respondentssample. Data collection used questionnaire. Data, then, is processed with editing,coding, scoring, tabulating and analyzed using Spearman Rank.From the result of study, it shows that rs calculation (0,54) >rstable (0,45) H0 is rejected and Hi is accepted. It means there is correlation betweenfamily knowledge with hypertension diet with pursuance to give hypertension dietto the elder. Family pursuance in giving hypertension diet is 65%. Keywords: Knowledge, Hypertension Diet.